2022
DOI: 10.1007/s00402-022-04346-z
|View full text |Cite
|
Sign up to set email alerts
|

Full endoscopic anterior intrapelvic plate osteosynthesis: a cadaveric feasibility study

Abstract: In this investigation, it was assumed that it must be possible to visualize the intrapelvic aspect as accustomed by pelvic surgeons using the anterior intrapelvic (modified Stoppa) approach. Moreover, it was hypothesized, that plate mountings will not only be possible for the symphysis but also at the supra- and infrapectineal aspect as well as to the posterior column. Ten anonymized cadaveric specimens were included in this study. A standard laparoscopic totally extraperitoneal (TEP) approach was used. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…In fact, David et al ( 16 ) demonstrated recently that an extraperitoneal endoscopic dissection of the pelvis offers a similar visibility when compared to an open approach ( 16 ). Moreover, Hartel et al ( 17 ) introduced in a cadaver study a fully endoscopic approach for anterior intrapelvic surgery and plate osteosynthesis ( 17 ). However, to ensure successful osteosynthesis, especially with such a minimally invasive approach, a feasible implant technology is required.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, David et al ( 16 ) demonstrated recently that an extraperitoneal endoscopic dissection of the pelvis offers a similar visibility when compared to an open approach ( 16 ). Moreover, Hartel et al ( 17 ) introduced in a cadaver study a fully endoscopic approach for anterior intrapelvic surgery and plate osteosynthesis ( 17 ). However, to ensure successful osteosynthesis, especially with such a minimally invasive approach, a feasible implant technology is required.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, fixation of the anterior column is performed by plate and screw osteosyntheses and fixation of the posterior column by an antegrade posterior column screw via an ilioinguinal approach as a standard [ 18 24 ]. In the last few years, a trend towards less invasive techniques in acetabular fracture surgery could be observed [ 25 28 ]. The use of less invasive approaches has been proven to be beneficial, especially in geriatric patients, which is why the ilioinguinal approach has been replaced by the modified Stoppa (AIP) approach as well as the Pararectus approach [ 18 , 23 , 25 , 28 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, a trend towards less invasive techniques in acetabular fracture surgery could be observed [ 25 28 ]. The use of less invasive approaches has been proven to be beneficial, especially in geriatric patients, which is why the ilioinguinal approach has been replaced by the modified Stoppa (AIP) approach as well as the Pararectus approach [ 18 , 23 , 25 , 28 32 ]. However, the implantation of an antegrade posterior column screw requires an additional small incision to the first ilioinguinal window, if the plate osteosynthesis is performed via the modified Stoppa approach, while this will be not necessary with the Pararectus approach [ 19 , 21 , 31 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of intraoperative imaging, several alternative less traumatic fixation methods have been recently introduced and gained popularity as they could reduce operative time and morbidity. Minimally invasive [10] or endoscopic plate fixation [11,12], percutaneous cannulated screw fixation (PCSF) [8,13], Endobutton technique for dynamic fixation [10], and tape suture fixation [14] promise not only adequate stability of the disrupted anterior pelvic ring but also smaller skin incisions, less soft tissue trauma, and minimal blood loss [2]. However, published reports of PCSF for SPD are quite rare, and the overall value and superiority of the technique remain unclear.…”
Section: Introductionmentioning
confidence: 99%